Role of corticotropin-releasing factor neurotransmission in the lateral hypothalamus on baroreflex impairment evoked by chronic variable stress in rats - Barretto-de-Souza, Lucas [UNESP]; Benini, Ricardo [UNESP]; Reis-Silva, Lilian L. [UNESP]; Busnardo, Cristiane [UNESP]; Crestani, Carlos C. [UNESP] (Springer Nature, 2024)
Despite the importance of physiological responses to stress in a short-term, chronically these adjustments may be harmful and lead to diseases, including cardiovascular diseases. The lateral hypothalamus (LH) has been reported to be involved in expression of physiological and behavioral responses to stress, but the local neurochemical mechanisms involved are not completely described. The corticotropin-releasing factor (CRF) neurotransmission is a prominent brain neurochemical system implicated in the physiological and behavioral changes induced by aversive threats. Furthermore, chronic exposure to aversive situations affects the CRF neurotransmission in brain regions involved in stress responses. Therefore, in this study, we evaluated the influence of CRF neurotransmission in the LH on changes in cardiovascular function and baroreflex activity induced by chronic variable stress (CVS). We identified that CVS enhanced baseline arterial pressure and impaired baroreflex function, which were followed by increased expression of CRF2, but not CRF1, receptor expression within the LH. Local microinjection of either CRF1 or CRF2 receptor antagonist within the LH inhibited the baroreflex impairment caused by CVS, but without affecting the mild hypertension. Taken together, the findings documented in this study suggest that LH CRF neurotransmission participates in the baroreflex impairment related to chronic stress exposure.
Keywords: Autonomic activity; Cardiovascular; CRF; Emotion; Hypertension; Hypothalamus